UPAYA GURU MATA PELAJARAN AL-QUR’AN HADIST DALAM MENGATASI KESULITAN SISWA MEMBACA AL-QUR’AN DI MTs. RAUDLATUL ULUM NGIJO KARANGPLOSO MALANG - Nuuril Huda Afrina; Fathurrahman Alfa; Khoirul Asfiyak (Vicratina : Jurnal Ilmiah Keagamaan, 2020)
This thesys based on the result of temporary observation,which are helded at Mts Raudlatul Ullum Ngijo Malang, founding few student who haven’t read Al-qur’an well, they have any difficult to reading and understanding qur’anic terms. The main problem for students is : there is no supporting and advising from their parents, even mother or father. Beside the family’s supporting problem, bad habit and bad environtment of the student, make the first problem more real